Satellite observations of daytime and nighttime ozone in the mesosphere and lower thermosphere - Kaufmann, M.; Gusev, O. A.; Grossmann, K. U.; Martín-Torres, F. J.; Marsh, D. R.; Kutepov, A. A. (Journal of Geophysical Research: Atmospheres, 2003)
[1] The global distribution of mesospheric and lower thermospheric ozone 9.6 mum infrared emissions was measured by the Cryogenic Infrared Spectrometers and Telescopes for the Atmosphere (CRISTA) experiment during two Space Shuttle missions in November 1994 and August 1997. The radiances measured by CRISTA have been inverted to O-3 number densities in the 50-95 km range by using a nonlocal thermodynamic equilibrium model. A detailed sensitivity study of retrieved O-3 number densities has been carried out. The ozone abundance profiles show volume mixing ratios of 1-2 ppmv at the stratopause, 0.5 ppmv or less around 80 km, and typically 1 ppmv during daytime and 10 ppmv during nighttime at the secondary maximum. The agreement with other experiments is typically better than 25%. The global distribution of upper mesospheric ozone shows significant latitudinal gradients and an enhancement in the equatorial upper mesosphere. At the polar night terminator a third ozone maximum is observed. Three-dimensional model results indicate that the latitudinal gradients are significantly influenced by solar tides.